Perish the thawed? EDTA reduces DNA degradation during extraction from frozen tissue - Ella Messner; Lev Becker; Mia L. DeSanctis; Elizabeth A. Soranno; Ryan Pianka; Caileigh Pierce; Molly Johnson; Rosalia Falco Poulin; Hannah J. Appiah-Madson; Daniel L. Distel (PLoS ONE, 2025)
Cryopreservation is the gold standard for preserving high molecular weight (HMW) DNA (>10 kb) in tissue samples. However, frozen tissues are typically thawed either before or during DNA extraction, which can lead to substantial DNA degradation. In this study, we thawed the previously frozen tissues of 10 marine species (five fishes and five invertebrates) in the preservatives EDTA (250 mM, pH 10) or ethanol (EtOH, 95%) and maintained them in their respective preservatives overnight at 4°C before DNA extraction. We then compared the recovery of HMW DNA in these extracts to extracts prepared directly from frozen tissues. To evaluate the effect of these treatments on HMW DNA recovery, we determined the percentage of high molecular weight DNA (%HMW) and yield of HMW DNA normalized by tissue weight (nY) in each DNA extract. The average %HMW values for eight of the 10 species and the average nY values for five of the 10 species were significantly higher in extracts from EDTA-treated tissues compared to extracts from untreated frozen tissues. For all 10 species, we observed no significant decreases in average %HMW or nY values in extracts of EDTA-thawed tissues compared to those extracted directly from frozen tissues. In contrast, EtOH treatment did not significantly improve the average %HMW or nY values in extracts from tissues of nine of the 10 species when compared to extracts prepared directly from frozen tissues. Therefore, investigators may consider EDTA treatment as a simple method for improving HMW DNA recovery from frozen tissues.